A new diaryl 1, 2-diketone from the heartwood of Dalbergia latifolia. Issue 1 (2nd January 2018) - Liu, Rong-hua; Wang, Ding-qing; Zhang, Pu-zhao; Shao, Feng; Chen, Lan-ying; Huang, Hui-lian; Lin, Shuai
Abstract: A new diaryl 1, 2-diketone, named 1-(2, 5-dihydroxy-4-methoxyphenyl)-2-phenylethane-1, 2-dione(1), along with eight known compounds(2–9), were isolated from the heartwood of Dalbergia latifolia . They were identified on the basis of spectral data. Compounds1–7 were obtained from the Dalbergia genus for the first time. Compounds8 and9 were firstly isolated from the plant. Compound1 exhibited inactive against Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 21530 with the minimum inhibitory concentrations of 10.0 and 10.0 mg/mL, respectively. Abstract :